IoT Based Smart Door Lock With QR Code Access: Kunci Pintu Pintar Berbasis IoT dengan Akses Kode QR - Irsyad Nafi Afriadi; Izza Anshory (Indonesian Journal of Innovation Studies, 2025)
General Background The development of digital technology has enabled more advanced and practical home security systems. Specific Background Smart door lock systems are increasingly used to replace conventional locks due to their flexibility and remote control capabilities. Knowledge Gap Existing systems often rely on single authentication methods and lack integrated control through mobile applications and IoT connectivity. Aims This study aims to design and implement a prototype smart door lock system using QR code authentication integrated with an IoT platform. Results The system utilizes NodeMCU ESP8266, relay modules, solenoid door lock, and Blynk application, showing successful operation with WiFi control at a distance of 9 meters with obstacles and 11 meters without obstacles, and an average response delay of 1.1 seconds. Novelty The integration of QR code authentication with Blynk-based IoT control provides a combined access and remote control mechanism within a single system. Implications This system offers a practical solution for improving home security with remote access and real-time control through mobile devices. Keywords: Smart Door Lock, Internet of Things, QR Code, NodeMCU ESP8266, Blynk Key Findings Highlights System operates reliably within limited wireless range conditions Command execution shows consistent response time under testing scenarios Integrated authentication and remote control functions operate in one platform